Two new species of the genus Euxiphidiopsis Gorochov, 1993 (Orthoptera: Meconematinae) from China - Shi, Fu-Ming; Han, Li; Mao, Shao-Li; Bai, Jin-Rong (Zootaxa, 2014)
The article reported two new species of the genus Euxiphidiopsis Gorochov, 1993, i.e. Euxiphidiopsis erromena Shi & Mao sp. nov., and Euxiphidiopsis damingshanensis sp. nov. The type material is deposited in the Museum of Hebei University, Baoding, P. R. China.